Local Proliferation of Macrophages Contributes to Obesity-Associated Adipose Tissue Inflammation - Amano, Shinya U.; Cohen, Jessica L.; Vangala, Pranitha; Tencerova, Michaela; Nicoloro, Sarah M.; Yawe, Joseph C.; Czech, Michael P.; Aouadi, Myriam (Cell metabolism, 2014)
Adipose tissue (AT) of obese mice and humans accumulates immune cells, which secrete cytokines that can promote insulin resistance. AT macrophages (ATMs) are thought to originate from bone-marrow-derived monocytes, which infiltrate the tissue from the circulation. Here, we show that a major fraction of macrophages unexpectedly undergo cell division locally within AT, as detected by Ki67 expression and 5-ethynyl-2′-deoxyuridine incorporation. Macrophages within the visceral AT (VAT), but not those in other tissues (including liver and spleen), displayed increased proliferation in obesity. Importantly, depletion of blood monocytes had no impact on ATM content, whereas their proliferation in situ continued. Treatment with monocyte chemotactic protein 1 (MCP-1) induced macrophage cell division in AT explants, whereas mcp-1 deficiency in vivo decreased ATM proliferation. These results reveal that, in addition to blood monocyte recruitment, in situ proliferation driven by MCP-1 is an important process by which macrophages accumulate in the VAT in obesity.
Keywords: Obesity-Associated Adipose Tissue Inflammation; Local Proliferation; Macrophages